Handbook of research on reading comprehension (Routledge, 2009)
The Handbook of Research on Reading Comprehension assembles researchers of reading comprehension, literacy, educational psychology, psychology, and neuroscience to document the most recent research on the topic. It summarizes the current body of research on theory, methods, instruction, and assessment, including coverage of landmark studies. Designed to deepen understanding of how past research can be applied and has influenced the present and to stimulate new thinking about reading comprehension, the volume is organized around seven themes: historical perspectives on reading comprehension, theoretical perspectives,...